Early neonatal mortality rate and the risk factors in Wangaya hospital - Made lndah Nastiti Utami Budha; Wayan Retayasa; Made Kardana (Indonesian Pediatric Society, 2008)
Background The first week of life of a neonate is a critical period.In Asia, early neonatal mortality rate remains high.Objective To investigate early neonatal mortality rate and the riskfactors in Wangaya Hospital.Methods A cross sectional study was carried out retrospectivelyon neonates registered at Perinatology Unit, Wangaya HospitalDenpasar, Bali since January 2006. The study was done fromOctober to November 2007. Data was obtained from medicalrecord, analyzed as univariate using chi-square test or Fisher'sexact test and multivariate logistic regression analysis model.Results Early neonatal mortality rate in Wangaya Hospital was 38.7per 1000 livebirths. Univariate analyses showed that there werefive significant risk factors of early neonatal death, i.e., respiratorydistress, asphyxia, birth weight less than 2500 grams, sepsis, andgestational age less than 3 7 weeks. Multivariate analysis showedthat those five variables were significant as risk factors of earlyneonatal death i.e., OR (95% confidence interval) for respiratorydistress: 16.8 (3.7 to 76.6)], asphyxia: 13.5 (6.1 to 29.9)], birthweight <2500 grams: 8.1 (3.3 to 19.9)], sepsis: 7.3 (3.1 to 17.1),and gestational age <37 weeks: 3.5 (1.6 to 7.8)].Conclusions Early neonatal mortality rate in Wangaya Hospitalremains high. Respiratory distress, asphyxia, birth weight <2500gram, sepsis, and gestational age <37 weeks were independent riskfactors of early neonatal death.